If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -1) = 39 Reorder the terms: 3(-1 + 4x) = 39 (-1 * 3 + 4x * 3) = 39 (-3 + 12x) = 39 Solving -3 + 12x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 12x = 39 + 3 Combine like terms: -3 + 3 = 0 0 + 12x = 39 + 3 12x = 39 + 3 Combine like terms: 39 + 3 = 42 12x = 42 Divide each side by '12'. x = 3.5 Simplifying x = 3.5
| 4(3x+8)= | | 5x-15=100 | | c^2=18-3c | | -2x^2-3x-1=0 | | 2v^2+11v+5v= | | y(y+2)+(t+2)-9=0 | | 5c-7+17= | | -(3z-1)-2(z+9)=7(z+1) | | 22y-7x+3-2y+x= | | 2x^2+x=45 | | 6x-2=18x+2 | | 4x+20=7x+5 | | 3x-2x+3=0 | | x+(70000*.09)=70000 | | (v-1.4)(v+1.4)= | | 25v^2-49= | | 9(x+11)+5(13x)=0 | | (-1-2m)(5-3m)= | | x+3y=776 | | 7y+2=51 | | 12x^2-16x-3=0 | | 5a^2+24a-5= | | x+y=250 | | 2x-9=-8 | | 2*-9=-8 | | 3p^2=-4p-1 | | 3x^2=4x+11 | | 2x+5y=1252x-y-10 | | 2x+5y=125 | | -4y=12x+13 | | 30*8.50*52= | | -4x-6+x=-2x-x-10 |